Pemberdayaan Perempuan melalui Kegiatan Ekonomi Kreatif - Abdurraafi’ Maududi Dermawan (Raheema, 2016)
The position and condition of women in Indonesia are considerably far from men, especially in some aspects of life as social, politics, economics, education, and culture. This phenomenon, furthermore, portrays that women is still in a marginal state. Therefore, there should be a special treatment to avoid such problems. The women themselves could gain a special care seriously. They could work on creative economy sectors, for instance because of 14 aspects of creative economy that will be introduced in this article.